2008
DOI: 10.1136/adc.2007.125641
|View full text |Cite
|
Sign up to set email alerts
|

Rise in childhood obesity with persistently high rates of undernutrition among urban school-aged Indo-Asian children

Abstract: Background:Childhood obesity is an emerging global public health challenge. Evidence for the transition in nutrition in Indo-Asian developing countries is lacking. We conducted these analyses to determine the trends in nutritional status of school-aged children in urban Pakistan.Methods:Data on the nutritional status of children aged 5 to 14 years from two independent population-based representative surveys, the urban component of the National Health Survey of Pakistan (NHSP; 1990–1994) and the Karachi survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
112
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 34 publications
16
112
8
Order By: Relevance
“…It is well documented that the physical activity is inversely related to overweight and obesity in children and all age groups (Jafar et al, 2008).Physical inactivity during the early years of life is currently indicated as a major contributor to the increasing levels of obesity, and other serious medical conditions, seen in children and adolescents (Speiser et al, 2005). The present study showed a significant association between lower BMI scores among the included subjects and practicing physical activities during leisure times.…”
Section: Discussionsupporting
confidence: 58%
“…It is well documented that the physical activity is inversely related to overweight and obesity in children and all age groups (Jafar et al, 2008).Physical inactivity during the early years of life is currently indicated as a major contributor to the increasing levels of obesity, and other serious medical conditions, seen in children and adolescents (Speiser et al, 2005). The present study showed a significant association between lower BMI scores among the included subjects and practicing physical activities during leisure times.…”
Section: Discussionsupporting
confidence: 58%
“…1 Handgrip strength (HGS) is a reliable clinical parameter to assess nutritional status and physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…2 Good nutrition is essential for preventing nutritional disorders and averting subsequent incidence of acute and chronic diseases in later life. [3][4][5] Failure to consume a nutritionally balanced diet at this decisive point in life not only arrests linear growth but also influences the psychomotor functioning of adolescents. 6 Numerous studies and reports [7][8][9][10][11] revealed that adolescents are at a greater risk of nutritional deficiencies and disorders due to their rapid body growth, unhealthy eating habits, psychological, mental and emotional pressures associated with body dissatisfaction and temptations to have a slimmer body.…”
mentioning
confidence: 99%